1945
DOI: 10.1017/s0022172400035956
|View full text |Cite
|
Sign up to set email alerts
|

Agglutination tests in the diagnosis of enteric fever in the inoculated

Abstract: 1. Early blood culture is the best method of laboratory diagnosis in the inoculated case of enteric fever, but agglutination tests may give useful information.2. In inoculated cases of enteric fever O and Vi agglutinins may be absent or present only at low titres. Steadily rising titres are not the rule and the titres more often fluctuate.3. Complete agglutination at titres over 1: 80 for TO, over 1: 40 for AO, or over 1: 10 for Vi is suggestive but not diagnostic of an active infection.4. Non-specific stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1948
1948
1952
1952

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In 35 control sera, 12 normal (W.R.) specimens and 23 from cases of definitely diagnosed non-enteric febrile illnesses, T ' O' titres of 1:400 were found four times and of 1:200 another six times. Wilson (1945), also working in India and using a similar technique, obtained higher figures for healthy inoculated men than most other workers. The recurrent annual inoculation of the subjects examined by Wilson and by the author may be a partial explanation of their findings.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…In 35 control sera, 12 normal (W.R.) specimens and 23 from cases of definitely diagnosed non-enteric febrile illnesses, T ' O' titres of 1:400 were found four times and of 1:200 another six times. Wilson (1945), also working in India and using a similar technique, obtained higher figures for healthy inoculated men than most other workers. The recurrent annual inoculation of the subjects examined by Wilson and by the author may be a partial explanation of their findings.…”
Section: Resultsmentioning
confidence: 64%
“…On this there is very little published evidence, and the data mentioned above are too meagre for consideration. Wilson (1945) found a T 'O' titre of 1:320 or over in 1-6 % of patients with diseases other than enteric as. compared with 0-5% of healthy inoculated individuals.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Although a rise in serum titre was not found in every case, the results indicated that chloramphenicol does not interfere markedly with agglutinin production. Wilson (1945) and Mole (1948) investigated the agglutinin titre in the serum of inoculated persons with enteric fever who had not been treated with chloramphenicol. Their results were very variable; steadily rising titres were not the rule.…”
Section: Haloed Molesmentioning
confidence: 99%